An Urban Heritage Assessment with Panoramio, a Big-Data source. A Study of Downtown Bogotá - De Urbina, Amparo (Universidad del Rosario, 2021)
The proposal is part of the project of Amparo De Urbina in the doctorate in Social Studies, from the Externado University-Faculty of Social and Human Sciences. Its objective is to identify and characterize relevant urban settings in the center of Bogotá. Scenarios mediated by the collective perception of the local and foreign population from a relational perspective. This as an input to complement the current asset valuation. It seeks to make a reading of urban heritage, in the light of images of the center that some visitors reported daily to Panoramio between 2007 and 2014. Panoramio was a platform that until 2016 exhibited photographs of the places that the same users registered and georeferenced based on to their experiences in the territory. The results presented in this article show types of framing, location of the photographer and the evidence of some events typical of the city center.